Impaired Intestinal Permeability of Tricellular Tight Junctions in Patients with Irritable Bowel Syndrome with Mixed Bowel Habits (IBS-M) - Awad, Karem; Barmeyer, Christian; Bojarski, Christian; Nagel, Oliver; Lee, In-Fah M.; Schweiger, Michal R.; Schulzke, Jörg-Dieter; Bücker, Roland (Cells (Basel, Switzerland), 2023)
Background: The underlying pathophysiology of irritable bowel syndrome (IBS) is still unclear. Our aim was to investigate the pathophysiological mechanisms of diarrhea, constipation, and antigen uptake in mixed-type IBS (IBS-M). Methods: Colonoscopic biopsies were obtained from IBS-M patients. Epithelial transport and barrier function of colonic mucosae were characterized in Ussing chambers using impedance spectroscopy. Mucosal permeability to macromolecules was measured. Western blotting for tight junction (TJ) proteins was performed and their subcellular localization was visualized by confocal microscopy. RNA-sequencing was performed for gene expression and signaling pathway analysis. Results: In IBS-M, epithelial resistance and ENaC-dependent sodium absorption were unchanged, while short-circuit current reflecting chloride secretion was reduced. Concomitantly, epithelial permeability for fluorescein and FITC-dextran-4000 increased. TJ protein expression of occludin decreased, whereas claudins were unaltered. Confocal microscopy revealed the de-localization of tricellulin from tricellular TJs. Involved pathways were detected as proinflammatory cytokine pathways, LPS, PGE2, NGF, and vitamin D. Conclusions: Decreased anion secretion explains constipation in IBS-M, while ion permeability and sodium absorption were unaltered. Reduced occludin expression resulted in the delocalization of tricellulin from the tricellular TJ, leading to increased macromolecular permeability that contributes to antigen influx into the mucosa and perpetuates a low-grade inflammatory process.